(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The research focused on the formulation, optimization, characterization stabilization and in vitro evaluation of Mebendazole loaded solid lipid nanoparticles (MEB-SLN) using response surface methodology. MEB-SLN was developed using the melt-emulsification ultrasonication method. The optimized formulation contains Compritol 888 ATO as a solid lipid and Poloxamer 407 as a surfactant. The optimized MEB-SLN was spherical, and had an average size of 230.4nm, and zeta potential of -21.9mV. The physiochemical characterization included the evaluation of surface morphology, drug entrapment, x-ray diffraction studies, and differential scanning calorimetry. In vitro drug release studies revealed that MEB-SLN would release drugs for up to 24 hrs. The formulation was found to be significantly quite stable in the refrigerator than at room temperature, as per stability tests. As a result of these findings, MEB-SLN was identified as a possible drug carrier. This provides a framework for further exploration of the developed formulation.